Structural Strength Analysis of Car Deck Re-Layout Impact on Ro-Ro Ships Using Structural Analysis Method - Putra, Ferdie Hanafi; Priyambodo Nur Ardi Nugroho; Herijono, Boedi (Universitas Negeri Jakarta, 2025)
This study focuses on analyzing the structural strength of car deck construction in roll-on/roll-off (ro-ro) passenger ships. Ro-ro ships are designed to transport both vehicles and passengers, in which vehicles can drive in and out under their own power. While these ships are operational, there is a potential for improvement in their construction strength, particularly in the car deck area. The car deck is a critical structural component as it bears both vehicle loads and supports the upper decks. This research analyzes the car deck's structural integrity, which was initially designed for trucks and sport utility vehicles (SUV), under various conditions including calm water, sagging, and hogging scenarios. Using both finite element method (FEM) analysis through ANSYS software and manual calculations via Excel, the study evaluates maximum stress points and deflection. The 3D modeling was completed using Fusion 360, while 2D drawings were created in AutoCAD. Results revealed that the highest stress occurs during hogging conditions with truck loads, showing 188.23 MPa stress and 0.077128 m deflection. With a safety factor of 1.3281, these values comply with Indonesian Classification Bureau (BKI) standards, which require stress below 250 MPa and a safety factor above 1.